Generation of a human iPSC line CIBi010-A with a reporter for ASGR1 using CRISPR/Cas9 - Jian Fu (Stem Cell Research, 2022)
ASGR1 is a liver-specific surface marker that has been used to purify human pluripotent stem cell (PSC)-derived hepatocytes (iHeps). Furthermore, ASGR1+ iHeps represents a more mature subpopulation of iHeps. To utilize this marker for optimizing iHep differentiation and purification, we substituted the stop coden of ASGR1 with a fluorescent reporter protein mCherry in a human iPSC line iPSN0052 via CRISPR/Cas9-mediated homologus recombination. The generated CIBi010-A enableds us to monitor ASGR1 expression during hepatic differentiation and thus can be used to optimize our hepatic differentiation procedures.